MODERN CONCEPTS OF CONTROLLING AND ITS CONNECTION WITH THE ACCOUNTING SYSTEM - Sativaldieva Gulchehra Khudayberdievna (Scholar Express Journals, 2021)
In the article, the author considered controlling as a management system of countries with developed market economies and as an accounting and management and accounting and analytical tool for making and implementing management decisions along with accounting and analysis systems
Keywords: Controlling; accounting; management accounting; management